Tiktok Sebagai Ladang Apologetika Online Kontemporer - Senopati Salomo Olimbovo; Andries Yosua (Sekolah Tinggi Teologi Ekumene Jakarta., 2023)
The rapid development of technology and information in this era of globalization somehow affects the reality of believers in carrying out their ministry and starting from worship, evangelism, missions, even apologetics. Apologetics, originally done orally in the time of the apostles, then changed form into writing in the time of the Church Fathers, can now be done by utilizing existing social media. This article aims to analyze the dynamics, interactions, and advantages and disadvantages of apologetics online on social media, especially on the TikTok platform as one of the platforms favored by the people of Indonesia. The research method used is a qualitative approach, with literature studies as a theoretical foundation and data collection techniques. The results of this study illustrate that the social media platform TikTok, with its unique features, can be considered an efficient and effective medium for organizing apologetics ministries.